2022
DOI: 10.3390/land11091556
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Evolution Characteristics of Land Use/Cover and Its Driving Factor in Cambodia during 2000–2020

Abstract: Research on the spatial distribution and dynamic evolution of land use/cover (LUC) is the basis for land management and ecological protection. However, there is currently a lack of long-term analyses of the evolution of LUC at the national scale in Cambodia. Based on the GLC_FCS30 dataset, this paper analyzes the temporal and spatial evolution of LUC in Cambodia from 2000 to 2020, as well as its relationship with the country’s economic and social development and climate change using dynamic degree, flow direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Studies on LULC changes in Vietnam, Cambodia, and Laos also found that national economic development and human activities have a greater impact on LUCC in these countries. Among the factors that have a more pronounced impact are GDP, population, and urbanization rates [42,43,45]. Our research also shows that at the national scale, socio-economic and agricultural development have a greater impact on LUCC in Myanmar.…”
Section: Lucc and Its Influencing Factorssupporting
confidence: 51%
See 1 more Smart Citation
“…Studies on LULC changes in Vietnam, Cambodia, and Laos also found that national economic development and human activities have a greater impact on LUCC in these countries. Among the factors that have a more pronounced impact are GDP, population, and urbanization rates [42,43,45]. Our research also shows that at the national scale, socio-economic and agricultural development have a greater impact on LUCC in Myanmar.…”
Section: Lucc and Its Influencing Factorssupporting
confidence: 51%
“…The changing trend of LUCC in Myanmar is similar to that of other Indochina countries. Research by Hu et al [18], Zhang et al [42], and Niu et al [43] in Vietnam, Laos, Cambodia, and other countries also found the phenomenon of shrinking forests, shrubland, and the expansion of impervious surfaces.…”
Section: Lucc and Its Influencing Factorsmentioning
confidence: 99%
“…Studying the relationship between LULC changes and influencing factors is crucial for addressing issues related to the land system [40]. Research indicates that natural elements and economic factors are the primary drivers of LULC changes [41]. Their impact can be analyzed from both macro and micro perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Research methods have diversified. Earlier studies were primarily qualitative analyses; however, with the introduction of mathematical and statistical analysis methods, including principal component analysis (PCA), logistic regression models, and multiple regression models [23,40,41], these models can quantify the driving effects of LULC change drivers and have thus been widely applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation